Thyroid Functional Status in Chronic Kidney Disease - Hossain, Md Mosharruf; Shah, Kabiruzzaman; Begum, Nasrin; Ahmed, Parvez; Islam, AKM Monoarul; Chowdhury, Nurul Islam (Bangladesh Journal of Nuclear Medicine, 2018)
Objectives: This study was done to find out the effect of chronic kidney disease on thyroid functional status. Kidneys normally play an important role in the metabolism, degradation and excretion of thyroid hormones. Therefore, impairment in kidney function leads to disturbed thyroid physiology. All levels of the hypothalamic-pituitary-thyroid axis may be involved, including alterations in hormone production, distribution, and excretion. As a result, abnormalities in thyroid function tests are common in chronic kidney disease (CKD). Materials And Methods: A total of 100 patients suffering from different stages of chronic kidney disease were included for this study during the period of January 2010 to December 2010 at the Centre for Nuclear Medicine & Ultrasound, Rajshahi, Bangladesh. Results: This study showed high prevalence of primary hypothyroidism (11%), low T3 syndrome (45%) and subclinical hypothyroidism (5%) in chronic kidney disease patients. Furthermore, there is an increasing trend of decreased thyroid functional status along with decrease of estimated GFR (eGFR). Conclusions: Chronic kidney disease impairs thyroid functional status in different ways. Thyroid functional status evaluation is recommended in each and every patient of CKD. That can reduce the morbidity and mortality rate of CKD patients as well as reduce the social burden and health expenditure. Bangladesh J. Nuclear Med. 18(2): 141-144, July 2015